Spin Crossover Nanomaterials: From Fundamental Concepts to Devices. Issue 5 (24th November 2017) - Molnár, Gábor; Rat, Sylvain; Salmon, Lionel; Nicolazzi, William; Bousseksou, Azzedine
Abstract: Nanoscale spin crossover materials capable of undergoing reversible switching between two electronic configurations with markedly different physical properties are excellent candidates for various technological applications. In particular, they can serve as active materials for storing and processing information in photonic, mechanical, electronic, and spintronic devices as well as for transducing different forms of energy in sensors and actuators. In this progress report, a brief overview on the current state‐of‐the‐art of experimental and theoretical studies of nanomaterials displaying spin transition is presented. Based on these results, a detailed analysis and discussions in terms of finite size effects and other phenomena inherent to the reduced size scale are provided. Finally, recent research devices using spin crossover complexes are highlighted, emphasizing both challenges and prospects. Abstract : Spin crossover nanomaterials can serve as active elements for processing information and for transducing different forms of energy in sensors and actuators. The different physical mechanisms governing the spin transition at the nanoscale are summarized and the concept of spin‐state dependent surface energy is highlighted. Finally, photonic, electronic, and mechanical devices using spin crossover complexes are reviewed.